Declarative programming and knowledge management Conference on Declarative Programming, DECLARE 2019, Unifying INAP, WLP, and WFLP, Cottbus, Germany, September 9-12, 2019, Revised Selected Papers /: Conference on Declarative Programming, DECLARE 2019, Unifying INAP, WLP, and WFLP, Cottbus, Germany, September 9-12, 2019, Revised Selected Papers. (2020) - Unknown
No abstract available